The Effect of Work Environment, Reward, and Leadership Style on Work Discipline with Work Motivation as an Intervening Variable at PT. XYZ - Saputri, Rizka Dwi; Susanti, Riana; Adji, Askardija R. (Green Publisher Indonesia, 2026)
Work environment, reward, leadership style is a factor that influences work dicipline with work motivation as an intervening variable. With the work environment, reward and high leadership style is expected to be able to improve work dicipline with work motivation as an intervening variable. The variables in this study are the work motivation as an intervening variable. The variables used in this study are the work environment, reward, leadership style, work motivation anad work discipline. This study aims to determine the influence of the work environment, reward and leadership style on work discipline with work motivation as an intervening variable at PT. XYZ. This study used a quantitative approach. In this study, the population was 110 operator employees at PT. XYZ. The data processing method used in this study was the descriptive approach. Structural Equation Modeling (SEM) based Partial Least Squares (PLS) with the help of software SmartPLS3. The results of this study indicate that the work environment, reward and leadership style has a positive and significant partial influence on work motivation and work discipline. Work environment, reward and leadership style have a positive and significant influence simultaneously on work discipline with work motivation as an intervening variable. The implications of these findings can be used as a basis for improving a positive work environment, reward good and effective leadership style so that it can increase work motivation which in turn will encourage increased employee work discipline.